THE EFFECT OF COCOPEAT AND RICE HUSK PLANTING MEDIA HYDROPONICALLY ON THE GROWTH OF PALM OIL IN PRE NURSERY - Aulia Juanda Djaingsastro; Hardiansyah Sinaga; Ranto Mangasi Sitorus (Universitas Medan Area, 2021)
Palm oil can produce high productivity which must be supported from several aspects, one of them is a good and correct nursery. Palm oil nursery isusually carried out conventionally, namely planting using soil media. Hydroponic research using cocopeat and rice husks planting media on the growth of palm oil seeds in pre nursery has never been carried out. The objective of this study was to determine the growth of palm oil seedlings using the hydroponic method. This research was conducted in the STIPAP Medan greenhouse. This research was conducted from April to July 2018. This research was a non-factorial RAK, which consisted of four treatments, namely M0 (top soil), M1 (Cocopeat), M2 (rice husks), M3 (combination). Height, stem, number of leaves, dry and wet weight of roots and plants, root length were observed. Then data analysis with ANOVA with the continued test of 5% Duncan was performed. The results of the effect of cocopeat and rice husk media was there was no a significant effect on the treatment parameters of seed height, number of leaves, dry and wet weight of roots and plants, and root length.